Effects of environmental factors on dengue incidence in the Central Region, Burkina Faso: A time series analyses. - Jean Claude Romaric Pingdwindé Ouédraogo; Sylvain Ilboudo; Richard Joshua Tetteh; Charles Kyei; Siaka Lougué; Wendlasida Thomas Ouédraogo; Salfo Ouédraogo; David Dosoo; Kwaku Poku Asante; Léon Gueswendé Blaise Savadogo (PLoS Neglected Tropical Diseases)
Background Dengue is endemic in Burkina Faso with sporadic outbreaks during the decade 2011-2021. Dengue control depends on the ability to predict future outbreaks. This study aimed to forecast dengue cases using historical data between 2016 and 2021. Methods The study covered the Central Region, Burkina Faso, with dengue monthly data from the National System of Health Information (SNIS) and environmental data from the National Agency of Meteorology (ANAM). The Autoregressive Distributed Lag (ARDL) model was performed to forecast dengue cases between 2022 and 2025. Results Dengue cases increased gradually between 2016 and 2021, with seasonal spikes during the year. The 95 per cent confidence interval exceeds 5000 cases by 2023 and reaches about 10,000 cases by 2025. From the ARDL results, the lagged variable Dengue cases (-1) showed a strong positive association (coefficient = 0.76; p-value = 0.00) and the variable Dengue cases (-2) a negative association (coefficient = -0.47; p-value = 0.01). The Population statistically impacted dengue incidence (coefficient = 0.00; p-value of 0.01). Relative humidity (-1) and Relative humidity (-4) positively affected dengue cases (coefficient = 114.26; p-value = 0.00 and 90.84; p-value = 0.00 respectively). Furthermore, Rainfall (-4) had a negative influence on dengue incidence (Coefficient = -6.91; p-value = 0.00. D.Minimum temperature (-3) positively influenced dengue cases (Coefficient = 223.20; p-value = 0.01). D.Wind speed showed a negative relationship (Coefficient = -925.31; p-value = 0.02), while D. Wind speed (-3) had a positive relationship (Coefficient = 875.04; p-value = 0.02). In addition, the ARDL long-run results revealed a positive association between dengue cases and population size (p-value = 0.02), Relative humidity (p-value = 0.01), and D.Minimum temperature (p-value = 0.02), and a negative association with Rainfall (p-value = 0.04). Conclusion Dengue cases are forecasted to increase in the Central Region between 2022 and 2025. It is then crucial to develop long-term interventions against dengue, integrated with interventions for other neglected tropical diseases.